Laboratory and field investigation of chlorinated solvents remediation in soil and groundwater - Santharam, Sathishkumar (Kansas State University, 2008)
Chlorinated solvents are the second most ubiquitous contaminants, next to petroleum hydrocarbons, and many are carcinogens. Tetrachloroethylene or perchloroethene (PCE) has been employed extensively in the dry cleaning industry and carbon tetrachloride (CT) has been used as a fumigant in grain storage facilities. In this work, remediation feasibility studies were conducted by mesocosm experiments; a chamber was divided into six channels and filled with soil, and plants were grown on top. Each channel was fed with contaminated water near the bottom and collected at the outlet, simulating groundwater flow conditions. The contaminants were introduced starting from March 12, 2004. PCE was introduced at a concentration of about 2 mg/L ([similar to]12 [Mu]moles/L) in three channels, two of them with alfalfa plants and the other with grass. CT was introduced at a concentration of about 2 mg/L ([similar to]13 [Mu]moles/L) in the other three channels, two of them with alfalfa plants and the other with grass. After the system had attained steady state, the concentrations of PCE and CT at inlet and outlet were monitored and the amount of PCE and CT disappearing in the saturated zone was studied. Since no degradation products were found at the outlet after about 100 days, one channel-each for PCE and CT (with alfalfa) was made anaerobic by adding one liter of 0.2 % glucose solution. The glucose solution was fed once every month starting from July 1, 2004 and continued until February 2005. From October 1, 2004, one liter of 0.1 % emulsified soy oil methyl esters (SOME) was fed to two other channels (with alfalfa), one exposed to PCE and another exposed to CT. The SOME addition dates were the same as that for glucose. The outlet liquid of the channel fed with PCE and SOME started to contain some of the degradation compounds of PCE; however, the extent of degradation was not as great as that of the glucose fed channel. No degradation compounds were observed in the outlet solution of the channel (grass grown on top) in which no carbon and energy supplements were added. Similar trend was observed in the CT fed channels also. KB-1, a commercially available microbial culture (a consortium of dehalococcoides) that degrades dichloroethene (DCE), was added through the inlet of the PCE fed channels, but this did not lead to sufficient conversion of DCE. Addition of KB-1 at well 3, located approximately in the middle of the channel, had a greater impact in the degradation of DCE, in both glucose and SOME amended channels, compared to addition at the inlet. KB-1 culture added to the channel was active even 155 days later, suggesting that there is sustainable growth of KB-1 when provided with suitable conditions and substrates. A pilot field study was conducted for remediation of a tetrachloroethylene (PCE) contaminated site at Manhattan, KS. The aquifer in the pilot study area has two distinct zones, termed shallow zone and deep zone, with groundwater velocities of about 0.3 m/day and 0.1 m/day. Prior to the pilot study, PCE concentration in groundwater at the pilot study area was about 15 mg/L (ppm) in the deep zone and 1 mg/L in the shallow zone. Nutrient solution comprising soy oil methyl esters (SOME), lactate, yeast extract and glucose was added in the pilot study area for biostimulation, on August 18, 2005. Potassium bromide (KBr) was added to the nutrient solution as a tracer. PCE was converted to DCE under these conditions. To carry out complete degradation of PCE, KB-1, a consortium of Dehalococcoides, and a second dose of nutrient solution were added on October 13, 2005. After addition of KB-1, both PCE and DCE concentrations decreased. Nutrients were again injected on March 3, 2006 (with KBr) and on August 1, 2006. The total chlorinated ethenes (CEs) have decreased by about 80 % in the pilot study area due to bioremediation. Biodegradation of CEs continued for a long time (several months) after the addition of nutrients. The insoluble SOME may be retained at the feeding area and provide a long time source of electron donors. Biostimulation and bioaugmentation of PCE contaminated soil and groundwater was evaluated in the laboratory and this technique was implemented successfully in the pilot field study. Modeling of the tracer study was performed using an advection-dispersion equation (ADE) and traditional residence time distribution (RTD) methods. The dispersion coefficient, groundwater velocity and hydraulic conductivity were estimated from the experimental data. The groundwater velocities vary from 1.5 cm/d to 10 cm/d in the deep zone and 15 cm/d to 40 cm/d in the shallow zone. The velocities estimated from the 2004 tracer study and 2005 tracer study were higher compared to the velocity estimated from the 2006 tracer study, most likely because of microbial growth and product formation that reduced the hydraulic conductivity. Based on data collected from several wells the hydrologic parameter values obtained from tracer studies appear to vary spatially.
Keywords: Tetrachloroethene; Carbontetrachloride; Bioremediation; Soil and groundwater; Contaminant fate and transport; Chlorinated solvents; Biogeochemistry (0425); Engineering, Chemical (0542); Engineering, Environmental (0775)